Advances towards programmable droplet transport on solid surfaces and its applications. (5th June 2020) - Malinowski, Robert; Parkin, Ivan P; Volpe, Giorgio
Abstract : We review progress towards the programmable transport of droplets on surfaces together with its applications in chemistry and materials science. Abstract : Droplets moving on solid surfaces are at the heart of many phenomena of fundamental and applied interest in chemistry, physics and materials science. On the fundamental side, as they are often subject to evaporation, these droplets are a beautiful and complex example of non-equilibrium physical chemistry, whose explanation and understanding still capture the imagination of multiple researchers around the world. In technology, droplets on solid surfaces are of widespread use for handling small amounts of matter, for harvesting energy, for manufacturing materials and for sensing chemical and biological analytes. A key underlying factor of their widespread applicability is the degree of control that can be achieved over their transport on surfaces. This tutorial review provides an overview of recent progress towards the programmable transport of droplets on solid surfaces. We will first present the physical principles behind the main experimental strategies for droplet transport. We will then review the most inspiring applications where these strategies have been employed in chemistry, materials science and engineering. Finally, we will outline possible future research directions for the programmable transport of droplets. Beyond projecting the reader at the forefront of this exciting field of physical chemistry, we believe that this tutorial review will inspire diverse, multidisciplinary scientific communities to devise novel ways of manipulating the flow of matter, energy and information on solid surfaces using programmable droplets as vessels.